Results of a Research Evaluating Quality of Computer Science Education - Ján ZÁHOREC; Alena HASKOVÁ; Michal MUNK (Informatics in Education, 2012)
The paper presents the results of an international research on a comparative assessment of the current status of computer science education at the secondary level (ISCED 3A) in Slovakia, the Czech Republic, and Belgium. Evaluation was carried out based on 14 specific factors gauging the students' point of view. The authors present qualitative findings from the following nine analyzed factors: the popularity of computer science/informatics as a subject, the potential of using knowledge gained by studying informatics at school in everyday life, the attractiveness and demands of the curriculum content, the clarity and attractiveness of teacher presentation of the subject matter to students, the engagement of tasks solved while studying informatics, the degree of comprehensibility of informatics textbooks, and the usability of knowledge acquired in school for solving practical problems. Based on the results, the authors identify the strengths and weaknesses of computer science education in the observed countries.